2013
DOI: 10.1186/1471-2350-14-66
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene polymorphisms and serum cytokine levels in patients with idiopathic pulmonary fibrosis

Abstract: BackgroundStudies have demonstrated associations between cytokine gene polymorphisms and the risk of idiopathic pulmonary fibrosis (IPF). We therefore examined polymorphisms in the genes encoding interleukin (IL)-6, IL-10, interferon gamma (IFN-γ), tumor necrosis factor alpha (TNF-α), and transforming growth factor-beta 1 (TGF-β1), and compared the serum levels of these cytokines in IPF patients and healthy controls. Furthermore, we examined the association of the studied genotypes and serum cytokine levels wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 44 publications
4
16
0
1
Order By: Relevance
“…The haplotype frequencies are shown in Table 3; three haplotypes were identified. The genotype and haplotype frequencies of IL10 polymorphisms in the control group were consistent with previously published studies from different regions in Saudi Arabian [1,11] and European populations [20]. Polymorphisms at -819 and -592 positions were found in complete linkage disequilibrium (LD) as it has been reported previously in different populations [12,15].…”
Section: Distribution Of Il10 Polymorphisms In a Saudi Populationsupporting
confidence: 89%
“…The haplotype frequencies are shown in Table 3; three haplotypes were identified. The genotype and haplotype frequencies of IL10 polymorphisms in the control group were consistent with previously published studies from different regions in Saudi Arabian [1,11] and European populations [20]. Polymorphisms at -819 and -592 positions were found in complete linkage disequilibrium (LD) as it has been reported previously in different populations [12,15].…”
Section: Distribution Of Il10 Polymorphisms In a Saudi Populationsupporting
confidence: 89%
“…Nonetheless, its exact mechanism is yet unknown. Many studies have been done on changes causing lung damage at the cellular level (12)(13)(14). It is reported that the damage caused by reactive oxygen and nitrogen species, whose release is increased by activated infl ammatory cells, causing initiation of lipid peroxidation, hydroxylation, and nitrifi ying amino acids, has an important role in the pathogeny of lung fi brosis (15).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genetic delivery of IL-10 significantly attenuates the TGF- β production in the lung of mice with bleomycin-induced pulmonary fibrosis [ 48 ]. In humans greater percentage of peripheral CD4 + T lymphocytes produced IL-10 and higher serum levels of IL-10 were found in patients with IPF than normal subjects [ 49 ]. Moreover, the extent of IL-10 production correlated with forced vital capacity of the patients [ 120 ].…”
Section: Role Of Il-10 Family Members In Fibrotic Diseasesmentioning
confidence: 99%